THE CHALLENGES OF ADAPTING ENGLISH NOVEL IN SENIOR HIGH SCHOOLS IN INDONESIA - Elshita Octaverina Alfadhilah; Dwi Agustina (Universitas PGRI Palembang, 2025)
This study investigates the primary challenges faced by English teachers in adapting English novels for instruction in Indonesian senior high school EFL classrooms. It explores the difficulties encountered and suggests practical strategies to enhance the integration of literature into language teaching. Employing a descriptive qualitative design, data were collected via online structured questionnaires and semi-structured interviews, analyzed using Braun and Clarke’s (2006) thematic analysis framework. Participants were selected through purposive sampling from two senior high schools. Findings reveal that while teachers value adapted English novels for fostering language proficiency and cultural understanding, they face significant obstacles, including students’ limited reading competence, lack of instructional time, inadequate resources, and a curriculum that emphasizes functional English over literary study. Teachers commonly respond by simplifying texts and selecting more accessible literary content. This study contributes meaningful insights into the realities of literature adaptation in both vocational and general secondary EFL contexts in Indonesia. It offers practical implications for curriculum planners, educators, and policymakers by highlighting feasible classroom strategies and aligning literature use with existing curricular constraints. The research adds to current ELT literature by emphasizing context-specific pedagogical adaptations and advocating for more inclusive and literature-enriched English instruction.